Routes to Persuasion. Negotiating Attitudes in Contemporary Neo-Pentecostal Discourse - Berdowicz, Ewelina ('Ilu. Revista de Ciencias de las Religiones, 2025)
Since the 1980s, Christianity in Europe has undergone major changes which apply mostly to both the ritual and leadership style. The former stands for religious practices focused on evoking supernatural phenomena whose emergence aims to empower an individual to take a particular action whereas the latter concerns efficient management, based on the modus operandi typical of the corporate environment. John Wimber and Charles Peter Wagner are claimed to have been the key figures responsible for the aforementioned shift. Wimber introduced the so-called Signs and Wonders Movement, followed by a world-famous preaching strategy known as power evangelism. He gave rise to the birth of the Third Wave Pentecostalism, also recognized as Neo-Pentecostalism. Wagner on the other hand, initiated the New Apostolic Reformation (NAR), that is, a theological belief and movement at the same time whose core themes include transforming societies through strategic-level spiritual warfare (SLSW) and in consequence, advancing the kingdom of God. Interestingly, those two approaches complement each other what can be observed when exploring the discourse. The principal objective of this study is to investigate how the present-day Polish and Italian evangelists following the strategy of power evangelism negotiate attitudes and how it affects recipients’ self-image. Data were collected by means of participant observation, surveys as well as written and spoken text analysis.